Raising Awareness of Protected Marine Biota among Fishermen Groups in Lanto Village, Central Buton Regency - Rahmat Karim, S.Si., M.Si; Hasidu, La Ode Abdul Fajar; Prasetya, Arif (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
Limited awareness among fishermen regarding protected marine species remains a major challenge in marine conservation efforts in coastal areas. Lanto Village, Central Mawasangka District, Central Buton Regency, is a coastal community where most residents depend on fishing activities, resulting in frequent interactions with protected marine species. This community service activity aimed to enhance fishermen’s knowledge and awareness of protected marine species, including their identification, legal protection status, and ecological importance, through socialization and educational activities. The methods applied included a pre-test, oral presentations supported by visual media, interactive discussions, and a post-test to assess changes in participants’ understanding. The results indicated that prior to the activity, fishermen’s knowledge of protected marine species was generally low, particularly regarding legal regulations, protection status, and ecological reasons for conservation. Following the socialization process, a significant improvement was observed in fishermen’s ability to identify protected marine species and their awareness of the importance of marine ecosystem conservation. This activity demonstrates that participatory and context-based educational approaches are effective in increasing knowledge and fostering conservation awareness among coastal communities.